A feasibility study on establishing "3 G's Pinoy Cuisine" at Purok 3, Bacao 1, General Trias, Cavite - Del Rosario, Maria Isabel B., author; Lisama, Aimee T., author; Reyes, Dolly Sheina D., author; Ventura, Elizabeth A., adviser (Rosario, Cavite : Cavite State University-CCAT Campus, 2007)
Thesis Abstract
A Feasibility Study (BSHRM)--Cavite State University-CCAT Campus, 2007.
Includes bibliographical references and appendices.
In English text.
Keywords: Filipino cuisine; Filipino food; Affordable; Filipino dishes; Feasibility study